Sun-proof laminated glass for vehicle window and preparation method thereof
By adopting a sandwich structure of composite acrylic composite gel layer and reflective insulation film layer on the window glass, combined with KH151 modified ultraviolet barrier filler and multi-layer film layer technology, the problem of insufficient ultraviolet and infrared barrier performance of existing window glass is solved, and more effective thermal ray isolation and interior protection are achieved.
Patent Information
- Application Number
- CN202311831997.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-12-28
AI Technical Summary
The existing window glass has weak ultraviolet and infrared barrier properties, which leads to an increase in the temperature inside the car, affects the driving experience and accelerates the aging of the interior.
Using a sandwich structure including a composite acrylic composite gel layer, glass and reflective insulation film layer, a self-adhesive hydrogel is polymerized with acrylic acid, acrylamide and chitosan through KH151 modified ultraviolet barrier filler to form a self-adhesive hydrogel, and titanium dioxide, silica, and tin oxide antimony film layers are successively coated on the glass surface to construct a solar light filtration system.
It significantly improves the ultraviolet and infrared barrier properties of the car window glass, reduces the transmission of heat rays, forms a heat-insulating structure, reduces the interior temperature, and extends the service life of the interior.
Smart Images

Figure BDA0004636591760000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass, in particular to a sun-proof laminated glass for vehicle windows and a preparation method thereof. Background Art
[0002] As an indispensable part of a car, the glass exterior windows must meet the requirements of lighting, sunlight ventilation and vision. However, conventional car window glass is weak in the direction of UV and infrared blocking performance. After being exposed to the sun for a long time outdoors, a large amount of ultraviolet and infrared rays will enter the interior of the car, causing the temperature inside the car to rise rapidly, which not only affects people's driving experience, but also accelerates the aging of the interior, and is prone to peeling and other phenomena. More importantly, it will also emit bursts of odor. To solve this problem, people stick sunscreen films on the car windows. The sunscreen films on the market are mainly low-transmittance dark films. Although they can block sunlight and heat, this film sacrifices the requirements of the field of vision of the car window glass and affects the visibility at night, posing certain hidden dangers to travel. Summary of the invention
[0003] The object of the present invention is to provide a sun-proof laminated glass for vehicle windows and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a sun-proof laminated glass for vehicle windows, which comprises a composite acrylic composite gel layer, glass, and a reflective heat-insulating film layer from inside to outside.
[0005] Furthermore, the acrylic composite gel is prepared from KH151 modified UV blocking filler, acrylic acid, acrylamide and chitosan.
[0006] Furthermore, the UV blocking filler is prepared from 4-methoxycinnamic acid, 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde, p-aminobenzoic acid and magnesium aluminum hydrotalcite.
[0007] Furthermore, the reflective heat-insulating film layer is prepared by magnetron sputtering titanium dioxide, silicon dioxide, and antimony tin oxide on the glass surface in sequence.
[0008] Furthermore, a method for preparing a sun-proof laminated glass for a vehicle window comprises the following preparation steps:
[0009] (1) 8 to 12 parts of magnesium aluminum hydrotalcite, 2 to 5 parts of Schiff base compound, and 120 to 130 parts of ethylene glycol are stirred at 1000 to 1200 rpm for 15 minutes, heated to 70° C., stirred at 400 to 600 rpm for 4 to 7 hours, filtered while hot, and washed the filter cake with 80° C. distilled water until the filtrate is neutral, dried at 70° C. for 18 hours, and ground to a particle size of 60 to 120 nm to obtain a UV blocking filler;
[0010] (2) 1-4 parts of UV blocking filler, 30 parts of deionized water, and 0.9-2.1 parts of KH151 were mixed, stirred at 80-100 rpm for 20 hours, filtered, and dried at 60°C for 10 hours to obtain KH151 modified UV blocking filler; 0.2-0.6 parts of chitosan and 10-15 parts of deionized water were mixed, stirred at 100 rpm for 3-10 minutes, and then 0.005 parts of potassium persulfate, 1-3 parts of acrylamide, 0.2-0.6 parts of KH151 modified UV blocking filler, 0.04 parts of 2-hydroxy-2-methylpropiophenone, and 3-6 parts of acrylic acid were added, and the mixture was centrifuged at 8000 rpm for 5 minutes, and then poured into a mold and reacted at 60°C for 4-8 hours to obtain an acrylic acid composite gel;
[0011] (3) wiping the surface of the first glass with a thickness of 2.0 to 2.7 mm with alcohol, blowing it dry, and evenly coating the surface with acrylic composite gel, then placing a second glass with the same thickness on the gel layer, laminating the glass, and rolling it once at 60 to 100° C. and a pressure of 70 to 110 MPa to obtain a laminated glass with a thickness of 4.5 to 6.2 mm;
[0012] (4) Placing the laminated glass in a magnetron sputtering machine, and sequentially using a titanium dioxide target, a silicon dioxide target, and a tin oxide target doped with 6 mol% antimony, magnetron sputtering for 5 to 20 minutes, respectively, to obtain a sun-proof laminated glass for vehicle windows with a thickness of 5 to 7 mm.
[0013] Furthermore, the preparation method of the Schiff base compound in step (1) is as follows: 1 to 5 parts of a cinnamate compound, 0.7 to 2.1 parts of p-aminobenzoic acid and 16 parts of anhydrous ethanol are mixed, stirred to dissolve, stirred at 50 to 80 rpm for 30 minutes, 5 drops of glacial acetic acid are added, the temperature is raised to 65 to 70°C, reacted for 2 hours, cooled to room temperature, filtered, the filter cake is taken, and dried at -0.08 MPa and 60°C for 12 hours.
[0014] Furthermore, the preparation method of the cinnamate compound is as follows: after stirring and dissolving 7 to 11 parts of 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde, 10 to 14 parts of triethylamine, and 22 to 30 parts of dichloromethane, 16 to 20 parts of cinnamic acid chloride compound solution are added, wherein the mass ratio of cinnamic acid chloride compound to dichloromethane in the cinnamic acid chloride compound solution is 5:13.2, reacting at room temperature for 3 to 5 hours, and distilling at 300 to 400 rpm, vacuum degree -0.06 MPa, and 30°C until there is no liquid.
[0015] Furthermore, the preparation method of the acyl chloride cinnamic acid compound is: dissolving 10 to 15 parts of 4-methoxycinnamic acid in 40 parts of dichloromethane, cooling to 0°C under nitrogen protection, adding 5.0 to 7.8 parts of thionyl chloride, reacting for 2 to 4 hours, and distilling for 3 to 5 hours at a vacuum degree of -0.06 MPa and 25°C.
[0016] Furthermore, the preparation method of the magnesium aluminum hydrotalcite in step (1) is as follows: after stirring and dissolving 56 parts of 50% sodium hydroxide solution, 20 parts of sodium carbonate and 200 parts of distilled water, 225 to 230 parts of solution A are added at a temperature of 35° C. and a stirring speed of 200 to 300 rpm, wherein the mass ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and distilled water in solution A is 48 to 51:34 to 38:140, the temperature is raised to 60 to 70° C., reacted for 18 hours, cooled to room temperature, filtered, and the filter cake is washed with deionized water until the pH value of the washing liquid is 7.
[0017] Furthermore, the magnetron sputtering conditions in step (4) are as follows: the substrate temperature is room temperature, the sputtering power is 40 W, the sputtering gas argon flow rate is 20 sccm, and the deposition pressure is 0.4-1.0 Pa.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The present invention utilizes KH151 to modify the ultraviolet blocking filler, imparts double bonds to the surface, and then polymerizes with acrylic acid, acrylamide, and chitosan to form a self-adhesive hydrogel. The addition of acrylamide and chitosan promotes the adhesion ability of the hydrogel, so that the hydrogel can be used as an interlayer film to bond glass to form a laminated glass. Then, titanium dioxide, silicon dioxide, and antimony tin oxide film layers are sequentially sputtered and deposited on the surface of the laminated glass to form a three-layer composite film layer, thereby constructing a sunlight filtering system, reducing the transmission of ultraviolet and infrared rays, and greatly reflecting heat rays to form a heat insulation structure.
[0020] The ultraviolet blocking filler in the present invention is prepared from 4-methoxycinnamic acid, 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde, p-aminobenzoic acid and magnesium aluminum hydrotalcite. The present invention utilizes the carboxyl group of 4-methoxycinnamic acid to react with the hydroxyl group of 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde to form a cinnamate structure, which effectively absorbs ultraviolet light and preliminarily realizes the ultraviolet blocking performance of the laminated glass. Then, benzaldehyde and p-aminobenzoic acid form a Schiff base structure. When encountering ultraviolet light, the hydrogen atom proton on the phenolic hydroxyl group at the adjacent position of the Schiff base is transferred to the nitrogen atom, and the carbon-nitrogen double bond of the Schiff base is opened to form a large conjugated structure, which dissipates the energy of ultraviolet light and improves the ultraviolet blocking performance of the glass. In addition, the carboxyl group is intercalated in the magnesium aluminum hydrotalcite, and the ultraviolet shielding effect of the hydrotalcite is used to further enhance the ultraviolet blocking performance of the laminated glass. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the hydrogel and the sun-proof laminated glass for vehicle windows prepared in the following examples are as follows:
[0023] Hydrogel adhesion: The hydrogels of the examples and comparative examples were uniformly coated on glass with a thickness of 2.0 mm. The coating thickness was 0.2 mm and the test was performed according to GB / T1720.
[0024] UV shielding performance of hydrogel: Write on A4 paper with a UV pen, then cover the writing area with hydrogel, use a deuterium lamp to irradiate the hydrogel, and observe whether it is visible.
[0025] Sun protection: The sun protection laminated glass for vehicle windows of the embodiment and the comparative example was tested with reference to GB / T25261.
[0026] Transparency: The visible light transmittance of the sun-proof laminated glass for vehicle windows of the embodiment and the comparative example was measured using a UV-III ultraviolet-visible spectrophotometer.
[0027] Example 1
[0028] (1) Dissolve 10 parts of 4-methoxycinnamic acid in 40 parts of dichloromethane, cool to 0°C under nitrogen protection, add 5 parts of thionyl chloride, react for 2 hours, and distill for 3 hours at a vacuum degree of -0.06 MPa and 25°C to obtain a cinnamic acid chloride compound;
[0029] (2) After 7 parts of 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde, 10 parts of triethylamine, and 22 parts of dichloromethane were stirred and dissolved, 16 parts of cinnamic acid chloride compound solution were added, and the mass ratio of cinnamic acid chloride compound to dichloromethane in the cinnamic acid chloride compound solution was 5:13.2. After reacting at room temperature for 3 hours, distilling at 300 rpm, vacuum degree -0.06 MPa, and 30° C. until there was no liquid, to obtain a cinnamate compound;
[0030] (3) 1 part of cinnamate compound, 0.7 part of p-aminobenzoic acid and 16 parts of anhydrous ethanol were mixed, stirred to dissolve, stirred at 50 rpm for 30 min, and then 5 drops of glacial acetic acid were added. The mixture was heated to 65° C., reacted for 2 h, cooled to room temperature, filtered, and the filter cake was taken out and dried at -0.08 MPa and 60° C. for 12 h to obtain a Schiff base compound.
[0031] (4) After 56 parts of 50% sodium hydroxide solution, 20 parts of sodium carbonate and 200 parts of distilled water were stirred and dissolved, 225 parts of solution A were added at a temperature of 35° C. and a stirring speed of 200 rpm, wherein the mass ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and distilled water in solution A was 48:34:140, the temperature was raised to 60° C., reacted for 18 hours, cooled to room temperature, filtered, and the filter cake was washed with deionized water until the pH of the washing liquid was 7, to obtain magnesium aluminum hydrotalcite;
[0032] (5) 8 parts of magnesium aluminum hydrotalcite, 2 parts of Schiff base compound and 120 parts of ethylene glycol were stirred at 1000 rpm for 15 min, heated to 70° C., stirred at 400 rpm for 4 h, filtered while hot, and washed the filter cake with 80° C. distilled water until the filtrate was neutral, dried at 70° C. for 18 h, and ground to a particle size of 60 nm to obtain a UV blocking filler;
[0033] (6) 1 part of UV blocking filler, 30 parts of deionized water, and 0.9 parts of KH151 were mixed, stirred at 80 rpm for 20 hours, filtered, and dried at 60°C for 10 hours to obtain KH151 modified UV blocking filler; 0.2 parts of chitosan and 10 parts of deionized water were mixed, stirred at 100 rpm for 3 minutes, and then 0.005 parts of potassium persulfate, 1 part of acrylamide, 0.2 parts of KH151 modified UV blocking filler, 0.04 parts of 2-hydroxy-2-methylpropiophenone, and 3 parts of acrylic acid were added. After centrifugation at 8000 rpm for 5 minutes, the mixture was poured into a mold and reacted at 60°C for 4 hours to obtain an acrylic composite gel;
[0034] (7) Wiping the surface of the first glass with a thickness of 2.0 mm with alcohol, blowing it dry, and evenly coating the surface with acrylic composite gel, then placing a second glass with the same thickness on the gel layer, laminating the glass, and rolling it once at 60° C. and a pressure of 70 MPa to obtain a laminated glass with a thickness of 4.5 mm;
[0035] (8) The laminated glass was placed in a magnetron sputtering machine, and titanium dioxide target, silicon dioxide target, and tin oxide target doped with 6 mol% antimony were used in sequence. The magnetron sputtering was performed for 5 minutes respectively. The substrate temperature was room temperature, the sputtering power was 40 W, the sputtering gas argon flow rate was 20 sccm, the deposition pressure was 0.4 Pa, and the distance from the target to the glass was 8 cm. A sun-proof laminated glass for vehicle windows with a thickness of 5 mm was obtained.
[0036] Example 2
[0037] (1) Dissolve 12 parts of 4-methoxycinnamic acid in 40 parts of dichloromethane, cool to 0°C under nitrogen protection, add 6.2 parts of thionyl chloride, react for 3 hours, and distill for 4 hours at a vacuum degree of -0.06 MPa and 25°C to obtain a cinnamic acid chloride compound;
[0038] (2) After 9 parts of 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde, 12 parts of triethylamine, and 27 parts of dichloromethane were stirred and dissolved, 18 parts of cinnamic acid chloride compound solution were added, the mass ratio of cinnamic acid chloride compound to dichloromethane in the cinnamic acid chloride compound solution was 5:13.2, and the mixture was reacted at room temperature for 4 hours, and then distilled at 3500 rpm, vacuum degree -0.06 MPa, and 30° C. until there was no liquid, to obtain a cinnamate compound;
[0039] (3) 3 parts of cinnamate compound, 1.9 parts of p-aminobenzoic acid and 16 parts of anhydrous ethanol were mixed, stirred to dissolve, stirred at 65 rpm for 30 min, and then 5 drops of glacial acetic acid were added. The mixture was heated to 68° C., reacted for 2 h, cooled to room temperature, filtered, and the filter cake was taken out and dried at -0.08 MPa and 60° C. for 12 h to obtain a Schiff base compound.
[0040] (4) After 56 parts of 50% sodium hydroxide solution, 20 parts of sodium carbonate and 200 parts of distilled water were stirred and dissolved, 228 parts of solution A were added at a temperature of 35° C. and a stirring speed of 250 rpm, wherein the mass ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and distilled water in solution A was 50:36:140, the temperature was raised to 65° C., the reaction was continued for 18 hours, the solution was cooled to room temperature, filtered, and the filter cake was washed with deionized water until the pH of the washing solution was 7, thereby obtaining magnesium aluminum hydrotalcite;
[0041] (5) 10 parts of magnesium aluminum hydrotalcite, 3 parts of Schiff base compound and 125 parts of ethylene glycol were stirred at 1100 rpm for 15 min, heated to 70° C., stirred at 500 rpm for 5.5 h, filtered while hot, and washed the filter cake with 80° C. distilled water until the filtrate was neutral, dried at 70° C. for 18 h, and ground to a particle size of 90 nm to obtain a UV blocking filler;
[0042] (6) 2 parts of UV blocking filler, 30 parts of deionized water, and 1.5 parts of KH151 were mixed, stirred at 90 rpm for 20 hours, filtered, and dried at 60°C for 10 hours to obtain KH151 modified UV blocking filler; 0.4 parts of chitosan and 12 parts of deionized water were mixed, stirred at 100 rpm for 7 minutes, and then 0.005 parts of potassium persulfate, 2 parts of acrylamide, 0.4 parts of KH151 modified UV blocking filler, 0.04 parts of 2-hydroxy-2-methylpropiophenone, and 5 parts of acrylic acid were added. After centrifugation at 8000 rpm for 5 minutes, the mixture was poured into a mold and reacted at 60°C for 6 hours to obtain an acrylic composite gel;
[0043] (7) Wiping the surface of the first glass with a thickness of 2.3 mm with alcohol, blowing it dry, and evenly coating the surface with acrylic composite gel, then placing a second glass with the same thickness on the gel layer, laminating the glass, and rolling it once at 80° C. and a pressure of 90 MPa to obtain a laminated glass with a thickness of 5.3 mm;
[0044] (8) The laminated glass was placed in a magnetron sputtering machine, and titanium dioxide target, silicon dioxide target, and tin oxide target doped with 6 mol% antimony were used in sequence. The magnetron sputtering was performed for 12 minutes respectively. The substrate temperature was room temperature, the sputtering power was 40 W, the sputtering gas argon flow rate was 20 sccm, the deposition pressure was 0.7 Pa, and the distance from the target to the glass was 8 cm. A sun-proof laminated glass for vehicle windows with a thickness of 6 mm was obtained.
[0045] Example 3
[0046] (1) Dissolve 15 parts of 4-methoxycinnamic acid in 40 parts of dichloromethane, cool to 0°C under nitrogen protection, add 7.8 parts of thionyl chloride, react for 4 hours, and distill for 5 hours at a vacuum degree of -0.06 MPa and 25°C to obtain a cinnamic acid chloride compound;
[0047] (2) After 11 parts of 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde, 14 parts of triethylamine, and 30 parts of dichloromethane were stirred and dissolved, 20 parts of cinnamic acid chloride compound solution were added, the mass ratio of cinnamic acid chloride compound to dichloromethane in the cinnamic acid chloride compound solution was 5:13.2, and the mixture was reacted at room temperature for 5 hours, and then distilled at 400 rpm, vacuum degree -0.06 MPa, and 30° C. until there was no liquid, to obtain a cinnamate compound;
[0048] (3) 5 parts of cinnamate compound, 2.1 parts of p-aminobenzoic acid and 16 parts of anhydrous ethanol were mixed, stirred to dissolve, stirred at 80 rpm for 30 min, and then 5 drops of glacial acetic acid were added. The mixture was heated to 70° C., reacted for 2 h, cooled to room temperature, filtered, and the filter cake was taken out and dried at -0.08 MPa and 60° C. for 12 h to obtain a Schiff base compound.
[0049] (4) After stirring and dissolving 56 parts of 50% sodium hydroxide solution, 20 parts of sodium carbonate and 200 parts of distilled water, 230 parts of solution A were added at a temperature of 35° C. and a stirring speed of 300 rpm, wherein the mass ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and distilled water in solution A was 51:38:140, the temperature was raised to 70° C., reacted for 18 hours, cooled to room temperature, filtered, and the filter cake was washed with deionized water until the pH of the washing liquid was 7, to obtain magnesium aluminum hydrotalcite;
[0050] (5) 12 parts of magnesium aluminum hydrotalcite, 5 parts of Schiff base compound and 130 parts of ethylene glycol were stirred at 1200 rpm for 15 min, heated to 70° C., stirred at 600 rpm for 7 h, filtered while hot, and washed the filter cake with 80° C. distilled water until the filtrate was neutral, dried at 70° C. for 18 h, and ground to a particle size of 120 nm to obtain a UV blocking filler;
[0051] (6) 4 parts of UV blocking filler, 30 parts of deionized water, and 2.1 parts of KH151 were mixed, stirred at 100 rpm for 20 hours, filtered, and dried at 60°C for 10 hours to obtain KH151 modified UV blocking filler; 0.6 parts of chitosan and 15 parts of deionized water were mixed, stirred at 100 rpm for 10 minutes, and then 0.005 parts of potassium persulfate, 3 parts of acrylamide, 0.6 parts of KH151 modified UV blocking filler, 0.04 parts of 2-hydroxy-2-methylpropiophenone, and 6 parts of acrylic acid were added. After centrifugation at 8000 rpm for 5 minutes, the mixture was poured into a mold and reacted at 60°C for 8 hours to obtain an acrylic composite gel;
[0052] (7) wiping the surface of the first glass with a thickness of 2.7 mm with alcohol, blowing it dry, and then evenly coating the surface with acrylic composite gel, and then placing a second glass with the same thickness on the gel layer, laminating the glass, and rolling it once at 100° C. and a pressure of 110 MPa to obtain a laminated glass with a thickness of 6.2 mm;
[0053] (8) The laminated glass was placed in a magnetron sputtering machine, and titanium dioxide target, silicon dioxide target, and tin oxide target doped with 6 mol% antimony were used in sequence for magnetron sputtering for 20 minutes respectively. The substrate temperature was room temperature, the sputtering power was 40 W, the sputtering gas argon flow rate was 20 sccm, the deposition pressure was 1.0 Pa, and the distance from the target to the glass was 8 cm, thereby obtaining a sun-proof laminated glass for vehicle windows with a thickness of 7 mm.
[0054] Comparative Example 1
[0055] The difference between Comparative Example 1 and Example 2 is that there are no steps (1) and (2), and step (3) is changed to: 3 parts of 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde, 1.9 parts of p-aminobenzoic acid and 16 parts of anhydrous ethanol are mixed, stirred and dissolved, stirred at 65 rpm for 30 minutes, 5 drops of glacial acetic acid are added, the temperature is raised to 68°C, reacted for 2 hours, cooled to room temperature, filtered, the filter cake is taken, and dried at -0.08 MPa and 60°C for 12 hours to obtain a Schiff base compound. The remaining steps are the same as those of Example 2.
[0056] Comparative Example 2
[0057] The difference between Comparative Example 2 and Example 2 is that there is no step (3), and step (5) is changed to: 10 parts of magnesium aluminum hydrotalcite, 3 parts of cinnamate compound, and 125 parts of ethylene glycol are stirred at 1100 rpm for 15 minutes, heated to 70° C., stirred at 500 rpm for 5.5 hours, filtered while hot, and washed with 80° C. distilled water until the filtrate is neutral, dried at 70° C. for 18 hours, and ground to a particle size of 90 nm to obtain a UV blocking filler. The remaining steps are the same as those of Example 2.
[0058] Comparative Example 3
[0059] The difference between Comparative Example 3 and Example 2 is that there are no steps (4) and (5), and step (6) is changed to: 0.4 parts of chitosan and 12 parts of deionized water are mixed, stirred at 100 rpm for 7 minutes, 0.005 parts of potassium persulfate, 2 parts of acrylamide, 0.4 parts of Schiff base compound, 0.04 parts of 2-hydroxy-2-methylpropiophenone, and 5 parts of acrylic acid are added, centrifuged at 8000 rpm for 5 minutes, poured into a mold, and reacted at 60° C. for 6 hours to obtain an acrylic acid composite gel. The remaining steps are the same as those of Example 2.
[0060] Comparative Example 4
[0061] The difference between Comparative Example 4 and Example 2 is that step (6) is different. Step (6) is changed to: 2 parts of UV blocking filler, 30 parts of deionized water, and 1.5 parts of KH151 are mixed, stirred at 90 rpm for 20 hours, filtered, and dried at 60° C. for 10 hours to obtain KH151 modified UV blocking filler; 12 parts of deionized water are mixed, 0.005 parts of potassium persulfate, 2 parts of acrylamide, 0.4 parts of KH151 modified UV blocking filler, 0.04 parts of 2-hydroxy-2-methylpropiophenone, and 5 parts of acrylic acid are added, centrifuged at 8000 rpm for 5 minutes, poured into a mold, and reacted at 60° C. for 6 hours to obtain acrylic composite gel. The remaining steps are the same as in Example 2.
[0062] Comparative Example 5
[0063] The difference between Comparative Example 5 and Example 2 is that step (6) is different. Step (6) is changed to: 2 parts of UV blocking filler, 30 parts of deionized water, and 1.5 parts of KH151 are mixed, stirred at 90 rpm for 20 hours, filtered, and dried at 60°C for 10 hours to obtain KH151 modified UV blocking filler; 0.4 parts of chitosan and 12 parts of deionized water are mixed, stirred at 100 rpm for 7 minutes, and then 0.005 parts of potassium persulfate, 0.4 parts of KH151 modified UV blocking filler, 0.04 parts of 2-hydroxy-2-methylpropiophenone, and 5 parts of acrylic acid are added, centrifuged at 8000 rpm for 5 minutes, poured into a mold, and reacted at 60°C for 6 hours to obtain acrylic composite gel. The remaining steps are the same as in Example 2.
[0064] Comparative Example 6
[0065] The difference between Comparative Example 6 and Example 2 is that step (8) is different, and step (8) is changed to: placing the laminated glass in a magnetron sputtering machine, using titanium dioxide target and silicon dioxide target in turn, magnetron sputtering for 12 minutes respectively, the substrate temperature is room temperature, the sputtering power is 40W, the sputtering gas argon flow rate is 20sccm, the deposition pressure is 0.7Pa, the distance from the target to the glass is 8cm, and a sunscreen laminated glass for vehicle windows with a thickness of 6mm is obtained. The remaining steps are the same as those in Example 2.
[0066] Comparative Example 7
[0067] The difference between Comparative Example 7 and Example 2 is that step (8) is different. Step (8) is changed to: placing the laminated glass in a magnetron sputtering machine, using titanium dioxide target material and tin oxide target material doped with 6 mol% antimony in turn, magnetron sputtering for 12 minutes respectively, the substrate temperature is room temperature, the sputtering power is 40 W, the sputtering gas argon gas flow rate is 20 sccm, the deposition pressure is 0.7 Pa, the distance from the target material to the glass is 8 cm, and a sunscreen laminated glass for vehicle windows with a thickness of 6 mm is obtained. The remaining steps are the same as those in Example 2.
[0068] Comparative Example 8
[0069] The difference between Comparative Example 8 and Example 2 is that step (8) is different, and step (8) is changed to: placing the laminated glass in a magnetron sputtering machine, using silicon dioxide target material and tin oxide target material doped with 6 mol% antimony in turn, magnetron sputtering for 12 minutes respectively, the substrate temperature is room temperature, the sputtering power is 40 W, the sputtering gas argon gas flow rate is 20 sccm, the deposition pressure is 0.7 Pa, the distance from the target material to the glass is 8 cm, and a sunscreen laminated glass for vehicle windows with a thickness of 6 mm is obtained. The remaining steps are the same as those in Example 2.
[0070] Effect example
[0071] Table 1 below shows the performance analysis results of the hydrogels and sun-proof laminated glasses for vehicle windows using Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.
[0072] Table 1
[0073]
[0074] From the comparison of the experimental data of adhesion and appearance of the embodiment and the comparative example, it can be found that the present invention uses 4-methoxycinnamic acid, 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde and p-aminobenzoic acid to synthesize a compound integrating cinnamate and Schiff base structure, which effectively absorbs ultraviolet light, and with the help of the ultraviolet shielding effect of hydrotalcite, it is intercalated between layers to further enhance the ultraviolet blocking performance of the laminated glass, and then polymerized with acrylic acid, acrylamide and chitosan to form a hydrogel. The addition of acrylamide and chitosan promotes the adhesion ability of the hydrogel; from the comparison of the experimental data of sunlight reflectance and hemispherical reflectance of the embodiment and the comparative example, it can be found that the present invention sequentially coats titanium dioxide, silicon dioxide and antimony tin oxide film layers on the glass surface to construct a sunlight filtering system to reduce the transmission of ultraviolet and infrared rays.
[0075] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A sun-proof laminated glass for vehicle windows, characterized in that: The sun-proof laminated glass for vehicle windows comprises, from the inside to the outside, a composite acrylic composite gel layer, glass, and a reflective heat-insulating film layer; The sun-proof laminated glass for vehicle windows comprises the following preparation steps: (1) Dissolve 10-15 parts of 4-methoxycinnamic acid in 40 parts of dichloromethane, cool to 0°C under nitrogen protection, add 5.0-7.8 parts of thionyl chloride, react for 2-4 hours, and distill at -0.06 MPa and 25°C for 3-5 hours to obtain a cinnamic acid chloride compound; stir and dissolve 7-11 parts of 2-hydroxy-5-(2-hydroxyethyl)benzaldehyde, 10-14 parts of triethylamine, and 22-30 parts of dichloromethane, add 16-20 parts of a cinnamic acid chloride compound solution, the mass ratio of the cinnamic acid chloride compound to dichloromethane in the cinnamic acid chloride compound solution is 5:13.2, react at room temperature for 3-5 hours, and distill at 300-400 rpm, vacuum degree -0.06 MPa, and 30°C until there is no liquid to obtain a cinnamate compound; 1. cinnamate compound, 0.7-2.1 parts of p-aminobenzoic acid and 16 parts of anhydrous ethanol are mixed, stirred and dissolved, stirred at 50-80 rpm for 30 min, 5 drops of glacial acetic acid are added, the temperature is raised to 65-70°C, reacted for 2 h, cooled to room temperature, filtered, the filter cake is taken, vacuum degree -0.08 MPa, 60°C drying for 12 h to obtain a Schiff base compound; 8-12 parts of magnesium aluminum hydrotalcite and 2-5 parts of Schiff base compound and 120-130 parts of ethylene glycol are stirred at 1000-1200 rpm for 15 min, heated to 70°C, stirred at 400-600 rpm for 4-7 h, filtered while hot, and the filter cake is washed with 80°C distilled water while filtering until the filtrate is neutral, dried at 70°C for 18 h, and ground to a particle size of 60-120 nm to obtain a UV blocking filler; (2) 1-4 parts of UV blocking filler, 30 parts of deionized water, and 0.9-2.1 parts of KH151 were mixed, stirred at 80-100 rpm for 20 hours, filtered, and dried at 60°C for 10 hours to obtain KH151 modified UV blocking filler; 0.2-0.6 parts of chitosan and 10-15 parts of deionized water were mixed, stirred at 100 rpm for 3-10 minutes, and then 0.005 parts of potassium persulfate, 1-3 parts of acrylamide, 0.2-0.6 parts of KH151 modified UV blocking filler, 0.04 parts of 2-hydroxy-2-methylpropiophenone, and 3-6 parts of acrylic acid were added. After centrifugation at 8000 rpm for 5 minutes, the mixture was poured into a mold and reacted at 60°C for 4-8 hours to obtain acrylic acid composite gel; (3) Wipe the surface of the first glass with a thickness of 2.0~2.7mm with alcohol, blow dry it, and evenly coat the surface with acrylic composite gel. Then place the second glass with the same thickness on the gel layer, and combine them. Roll and press once at 60~100℃ and pressure of 70~110MPa to obtain a laminated glass with a thickness of 4.5~6.2mm. (4) The laminated glass is placed in a magnetron sputtering machine, and titanium dioxide target, silicon dioxide target, and tin oxide target doped with 6 mol% antimony are used in sequence for magnetron sputtering for 5 to 20 minutes, respectively, to obtain a sun-proof laminated glass for vehicle windows with a thickness of 5 to 7 mm.
2. The sun-proof laminated glass for vehicle windows according to claim 1, characterized in that: The preparation method of the magnesium aluminum hydrotalcite in step (1) is as follows: after stirring and dissolving 56 parts of a 50% sodium hydroxide solution, 20 parts of sodium carbonate and 200 parts of distilled water, 225-230 parts of solution A are added at a temperature of 35°C and a stirring speed of 200-300 rpm, wherein the mass ratio of magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and distilled water in solution A is 48-51:34-38:140, the temperature is raised to 60-70°C, reacted for 18 hours, cooled to room temperature, filtered, and the filter cake is washed with deionized water until the pH of the washing liquid is 7.
3. The sun-proof laminated glass for vehicle windows according to claim 1, characterized in that: The magnetron sputtering conditions in step (4) are as follows: the substrate temperature is room temperature, the sputtering power is 40 W, the sputtering gas argon flow rate is 20 sccm, and the deposition pressure is 0.4-1.0 Pa.
Citation Information
Patent Citations
Head-up display glass and head-up display system
CN114236839A